The use of reflexotherapy according to the method of "balancing hexagrams" in the complex rehabilitation of vertebrogenic lumboischialgia with long-term pain syndrome - Sereda, Vitaly; Svyrydova, Nataliа; Chupryna, Gennadii; Verner, Olga; Tordiya, Nadiya (My University, 2024)
The article raises the following topical issues – the topic of complex rehabilitation of vertebrogenic lumboischialgia with longterm pain syndrome. Various pathological conditions, especially those that occur with a pain syndrome, manifest themselves in a protracted course. It often happens when there is some viscerogenic problem that complicates the situation: then a psychosomatic component is formed, which prolongs the disease. Medicinal methods of treatment are then not fully effective, so non-medicinal technologies of comprehensive rehabilitation should be resorted to. Among such methods in the complex rehabilitation of vertebrogenic lumboschialgia with long-term pain syndrome, reflexology methods are respected. У статті піднімаються такі актуальні питання – тема комплексної реабілітації вертеброгенної люмбоішиалгії з тривалим больовим синромом. Різні патологічні стани, особливо ті, що протікають з больовим синдромом, проявляються затяжним перебігом. Часто це буває, коли є якась вісцерогенна проблема, що ускладнює ситуацію: тоді формується психосоматичний компонент, що й пролонгує захворювання. Медикаментозні методи лікування тоді не є повною мірою ефективними, тому слід вдаватися до немедикаментозних технологій комплексної реабілітації. Серед таких методів у комплексній реабілітації вертеброгенної люмбоішиалгії з тривалим больовим синромом користуються повагою методи рефлексотерапії.
Keywords: rehabilitation; реабілітація; reflexotherapy; рефлексотерапія; vertebrogenic lumboischialgia; вертеброгенна люмбоішиалгія